2009
DOI: 10.1088/0953-8984/21/18/183001
|View full text |Cite
|
Sign up to set email alerts
|

Silicon oxidation by ozone

Abstract: Understanding the oxidation of silicon has been an ongoing challenge for many decades. Ozone has recently received considerable attention as an alternative oxidant in the low temperature, damage-free oxidation of silicon. The ozone-grown oxide was also found to exhibit improved interface and electrical characteristics over a conventionally dioxygen-grown oxide. In this review article, we summarize the key findings about this alternative oxidation process. We discuss the different methods of O(3) generation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 88 publications
0
47
1
Order By: Relevance
“…Yet, there are only a limited number of papers that have investigated the initial stages of the O 3 reaction with H-terminated Si, where the reaction can be controlled near/at the atomic layer content [21]. A first principles investigation of the O 3 reaction on H-terminated Si indicated that the O atoms are mainly incorporated in the Si-H bonds with the formation of hydroxyl groups [21], which was not supported by our present investigation. Our model is in agreement with cluster based quantum chemical calculations illustrating that O inserted in the SiSi dimer bonds is the most likely structure at lower temperatures [51].…”
Section: Proposed Interface Si/o Bond Modelcontrasting
confidence: 82%
See 1 more Smart Citation
“…Yet, there are only a limited number of papers that have investigated the initial stages of the O 3 reaction with H-terminated Si, where the reaction can be controlled near/at the atomic layer content [21]. A first principles investigation of the O 3 reaction on H-terminated Si indicated that the O atoms are mainly incorporated in the Si-H bonds with the formation of hydroxyl groups [21], which was not supported by our present investigation. Our model is in agreement with cluster based quantum chemical calculations illustrating that O inserted in the SiSi dimer bonds is the most likely structure at lower temperatures [51].…”
Section: Proposed Interface Si/o Bond Modelcontrasting
confidence: 82%
“…We have also recently demonstrated the Si epitaxy from SiH 4 at 500 • C on an O atomic layer deposited using the surface reaction of O 3 on H-terminated Si(100)[14,20]. As opposed to the studies of Mears et al and of Tsu et al, O 3 is used as the O precursor instead of O 2 due to its higher reactivity with the H-terminated Si surface at lower temperatures[21][22][23]. A low deposition temperature can be beneficial for the fabrication of Si-O superlattices as the diffusion of O in Si is limited.…”
mentioning
confidence: 99%
“…As described in literature [4][5][6][7] ozone-grown oxides are found to exhibit improved interface (less strain, transition layer is reduced, high density and less defects due to more saturated Si-O bonds) and electrical properties due to the occurring damage-free oxidation of the silicon surface. In addition, it is assumed that atomic oxygen is the main driving force of the oxidation because it is the species that has the feature to be particularly diffusion active in the SiO x layer and saturate silicon dangling bonds [8].…”
Section: Introductionmentioning
confidence: 68%
“…Oxidation of ap-pSi to form oxidized pSi (ox-pSi) is one strategy that is used to stabilize the pSi PL, 4,25 and oxidation also provides a convenient pathway to tailor the pSi surface by using secondary derivatization strategies. 26,27 There have been many methods used to create ox-pSi, including rapid thermal oxidation, 28 hot water annealing, 29 anodic oxidation, 30 and oxidation by O 2 , 31 O 3 , 32 and hydrogen peroxide (H 2 O 2 ) 33 . H 2 O 2 oxidation is attractive because it is relatively safe and fast and can proceed at room temperature; it also does not require sophisticated apparatus.…”
Section: Introductionmentioning
confidence: 99%